2004
DOI: 10.1111/j.1468-2958.2004.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Deceit Via Analyses of Verbal and Nonverbal Behavior in Children and Adults

Abstract: This experiment examined children's and undergraduates' verbal and nonverbal deceptive behavior, and the extent to which their truths and lies could be correctly classified by paying attention to these responses. Participants (N = 196) aged 5-6, 10-11, and 14-15, as well as university undergraduates, participated in an erasing the blackboard event, and told the truth or lied about the event afterwards. Nonverbal and verbal responses were coded, the latter with Criteria-Based Content Analysis and Reality Moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
184
1
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(214 citation statements)
references
References 79 publications
14
184
1
15
Order By: Relevance
“…Nevertheless, some research suggests that lie-tellers tend to exhibit slightly more positive non-verbal behaviors, such as smiles, relaxed and confident facial expressions, and a positive tone of voice (Lewis et al, 1989). However, other research suggests that children have poor control of their non-verbal behavior, which points toward opposite and conflictive directions of what has been previously reported (Vrij et al, 2004; McCarthy and Lee, 2009). For instance, a study has reported that children between the ages of 7–9 years old show less eye contact when lying rather than when answering the truth while older children show longer eye contact, which is similar to what adults exhibit during a lying situation (McCarthy and Lee, 2009).…”
Section: Related Workcontrasting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, some research suggests that lie-tellers tend to exhibit slightly more positive non-verbal behaviors, such as smiles, relaxed and confident facial expressions, and a positive tone of voice (Lewis et al, 1989). However, other research suggests that children have poor control of their non-verbal behavior, which points toward opposite and conflictive directions of what has been previously reported (Vrij et al, 2004; McCarthy and Lee, 2009). For instance, a study has reported that children between the ages of 7–9 years old show less eye contact when lying rather than when answering the truth while older children show longer eye contact, which is similar to what adults exhibit during a lying situation (McCarthy and Lee, 2009).…”
Section: Related Workcontrasting
confidence: 58%
“…For instance, a study has reported that children between the ages of 7–9 years old show less eye contact when lying rather than when answering the truth while older children show longer eye contact, which is similar to what adults exhibit during a lying situation (McCarthy and Lee, 2009). Another study suggests a decrease of movement during a lie-tell, particularly on the hands and fingers (Vrij et al, 2004). …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Vrij, Akehurst, Soukara and Bull (2004) found significant differences in the expected direction regarding logical structure, amount of details, contextual information, descriptions of interaction, conversation reproduction, visual, audio, spatial and temporal details and cognitive operations. No effects were found however regarding mental state attributions, acknowledgement of lack of memory and doubts.…”
Section: Introductionmentioning
confidence: 99%
“…a) Mounting evidence (Bensi, Gambetti, Nori, & Giusberti, 2009;Campos & AlonsoQuecuty, 1998;Colwell, Hiscock-Anisman, Memon, Colwell, Taylor, & Woods, 2009;Comblain, D'Argembeau & Van der Linden, 2005;Diges, 1995;Diges, Rubio & Rodríguez, 1992;Henkel, Franklin & Johnson, 2000;Manzanero, El-Astal & Aróztegui, 2009;Memon, Fraser, Colwell, Odinot & Mastroberardino, 2010;Pérez-Mata & Diges, 2007;Roberts & Lamb, 2010) suggests that numerous factors (activation levels, coherence and previous knowledge, perceptual modality, subjects' involvement degree and perspective, age, contextual factors, type of design used in the research, training of the evaluators, and the coding method) influence the characteristics of statements. b) There is also great variability in the possible origins of memories and different sources produce distinctive characteristics which vary depending on whether they are from fantasy, lies, dreams or post-event information (Hekkanen & McEvoy, 2005;Johnson, Kahan & Raye, 1984;Sporer & Sharman, 2006;Vrij et al, 2004). c) Moreover, within each source there are different degrees on a continuum from perceptual memories to the most fantastic memories.…”
Section: Introductionmentioning
confidence: 99%